Ping weisan alleviates chronic colitis in mice by regulating intestinal microbiota composition. (12th June 2020) - Zhang, Zecai; Cao, Hongyang; Shen, Peng; Liu, Jiuxi; Cao, Yongguo; Zhang, Naisheng
Abstract: Ethnopharmacological relevance: Ping weisan (PWS), a complex formulation used in traditional Chinese medicine, is first described in 1107 AD and published in the Prescriptions of Taiping Benevolent Dispensary. We have previously confirmed that PWS has the effect of alleviating DSS-induced chronic ulcerative colitis (UC) in mice. Aim of the study: We aimed to examine whether PWS protects mice from chronic UC by regulating intestinal microbiota composition. Materials and methods: Chronic colitis was induced in C57BL/6 mice with 2.5% DSS in drinking water. PWS (8 g/kg) was orally administered throughout the experiment. Body weight changes, stool consistency and myeloperoxidase (MPO) activity were measured in these mice. Interleukin-17A (IL-17A) and interferon gamma (IFN-γ) mRNA levels were detected by qRT-PCR. The alterations of fecal microflora were investigated by 16S rRNA sequencing. Furthermore, intestinal tight junction protein including occludin, and serum lipopolysaccharide (LPS) level were also detected. Results: PWS relieved DSS-induced loss of body weight, and improved stool consistency and MPO activity in mice. The levels of IL-17A and IFN-γ mRNA were also reduced after treatment with PWS. PWS not only regulated occludin level but also decreased serum LPS. We further showed DSS-induced changes in intestinal microbial composition and richness are significantly regulated by PWS. PWS treatment significantly decreased the abundance of Bacteroidetes, but increased the abundance of Firmicutes in chronic UC mice induced by DSS. Conclusions: Combining with our previous results, we found that PWS could exert anti-UC role by rebalancing intestinal bacteria. Graphical abstract: Image 1